2D-cranial T1-black-blood MRI in suspected giant cell arteritis—measurement of vessel wall thickness does not give a diagnostic advantage compared to visual scoring alone - Seitz, Pascal; Bucher, Susana; Bütikofer, Lukas; Maurer, Britta; Bonel, Harald Marcel; Lötscher, Fabian; Seitz, Luca (Frontiers in Radiology, 2025)
ObjectivesTo compare two established scoring schemes for the 2D-T1-weighted “black-blood” MRI sequence (T1-BB) for superficial cranial arteries (SCA) in the diagnosis of giant cell arteritis (GCA).MethodsTen arterial segments were evaluated in T1-BB images with two different methods: a visual semiquantitative scheme (T1-BB-VISUAL) and a composite scheme that included both the semiquantitative assessment and a quantitative wall thickness measurement (T1-BB-COMP). The expert clinical diagnosis after ≥6 months of follow-up was the diagnostic reference standard. Diagnostic accuracy and agreement on the segment and patient levels were evaluated for the two different rating schemes.ResultsRetrospectively, 151 consecutive patients with clinically suspected GCA were included. The study cohort consisted of 82 patients with and 69 without GCA. For the T1-BB-COMP and the T1-BB-VISUAL, the sensitivity was 81.7% vs. 87.8% (p = 0.025), the specificity was 91.3% vs. 88.4% (p = 0.16) and the proportion of correct diagnoses was 86.1% vs. 88.1% (p = 0.26), respectively. The overall agreement between the two methods for 1,201 rated arterial segments was very good at 91.6% with a kappa of 0.80. The agreement was higher for segments with a larger calibre than for smaller segments: common superficial temporal arteries 98.0%, occipital arteries 93.2%, frontal branches 89.8% and parietal branches 86.9%. The correlation of wall thickness measurements between readers was strong (Spearman's rho of 0.68). The time needed to apply the T1-BB-VISUAL was about half as long as for the T1-BB-COMP (4.5 vs. 8.95 minutes).ConclusionIn suspected GCA, the additional measurement of the wall thickness of SCAs in 2D-T1-BB MRI does not lead to a better diagnostic performance compared to visual semiquantitative scoring alone. Visual scoring is preferred due to higher efficiency and reliability.